DIFFERENT NITRATE AND AMMONIUM LEVELS MEDIA ON CHANGES OF NITROGEN ASSIMILATION ENZYMES IN RICE - Handoyo, Tri; Ilman Widuri, Laily; Pudji Restanto, Didik (BIOVALENTIA: Biological Research Journal, 2021)
Nitrogen (N) is an important nutrient for the growth and development of rice plants, required in large quantity and often limiting factor of rice yields. The research was to understand the different sources and levels of nitrogen in rice plant on the activity of N assimilation enzymes, including nitrate reductase (NR), glutamine synthase (GS) content, glutamate synthase (Gogat) content, content, ammonium (NH4+) and nitrate (NO3-) content on the leaves. Paddy (Ciherang variety) was grown in sand media containing Hoagland solution with different sources (ammonium and nitrate) and levels (0.4, 0.8, 1.6, 3.2, 6.4, and 12.8 mM) of nitrogen. Nitrogen assimilation was observed from leaves at one month of age. The NR activity increased on both Nitrogen sources, it was a higher activity in media contained nitrate. Also, the activity of GS showed higher in media contains nitrate, but its activity was decreased after application 1.6 mM of nitrate and 3.2 mM of ammonium. Western blot analysis of GS1 and GS2 showed that the band pattern of protein was similar to these enzyme activities. Nitrate content in leaves gradually increased in both sources of nitrogen and higher than 3.2 mM ammonium application caused an increase in ammonium content in leaves, but the nitrate content decreased. This research resulted that the available source of N for rice was in nitrate form, easily by the rice plants during the growth stage.